Pembuatan Cerita Interaktif Menggunakan Scratch Untuk Meningkatkan Kreativitas Siswa MTs Pembangunan Nurul Islam - Ronald Sianipar; Dani Ramdani; Slamet; Denni Lesmana; Nurul Amin; Ari Pajri; Muhammad Irfan; Genta Ramadhan (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Scratch is a block-based visual programming language that is very suitable for beginners to create animations, games, and interactive stories. This community service program (PKM) aims to introduce interactive story making to students of MTs Pembangunan Nurul Islam. Activities are carried out through training, mentoring, and direct practice with a creative and fun approach. The results of the activities show an increase in student interest and creativity in using Scratch as a medium for digital expression. Interactive stories have also proven effective in fostering digital literacy, logical thinking, and problem-solving skills.